Toward effective implementation of the Regional Preparedness for Pest and Disease Outbreaks in West and Central Africa - Segnon, Alcade Christel; Obossou, Abrewa Remilokoun Esdras; Noumbo Tonle, Franck Bruno; Ganyo, Komla Kyky; Kpadonou, G Esaie; Lamien, Nieyidouba; Zougmore, Robert Bellarmin (2025)
Drawing insights from a regional stakeholder engagement workshop, this Info Note outlines actions identified for the effective implementation of the Regional Preparedness and Response Plan for pest and disease outbreaks in West and Central Africa. National Plant and Animal Health Protection experts from 20 countries in West and Central Africa found the regional plan highly relevant for their work. They also recognized the plan as a strategic tool for lobbying and fundraising to support implementation at the national level. Through case studies and participatory exercises, experts were able to translate the action plan into real-world actions and activities to manage pest and disease outbreaks in the region. Key priority actions identified for effective implementation of the regional plan, including consolidating tools and toolkits, high political engagement, national ownership, monitoring mechanisms, and partnerships at the national and regional levels. Scaling policy innovation requires multi-stakeholder engagement and institutional ownership. However, sustaining its adoption would depend on the availability of funding, adapted policy instruments, strong partnerships, and continuous adaptive learning. Therefore, deliberate investments and coordination mechanisms are needed to embed these innovations into national and regional systems.